Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

using the quadratic formula b²-4b+4=0


Sagot :

[tex]b^2-4b+4=0\\ (b-2)^2=0\\ b-2=0\\ b=2[/tex]
If you need to use  the Quadratic Formula, it could also look something like this:
(1)b² + (-4)b + (4) = 0
These represent a, b, and c in their respective order.
The equation itself is:
(-b (+/-) √(b² - 4ac))/2a
So, plug 'em in:
(4 (+/-) √(-4² - 4·1·4))/2·1
And then solve:
(4 (+/-) √(16 - 16))/2
(4 (+/-) 0)/2
4/2
2